Komponen-Komponen dalam Pengembangan Kurikulum Pendidikan Islam - Khoirun Nisa' (Muróbbî: Jurnal Ilmu Pendidikan, 2017)
The curriculum is everything that has been designated school for students in the school. The curriculum includes educational objectives, content and methods. The curriculum as a whole system has components that are interrelated between one and other, namely: objectives, content or material, methods, organization and evaluation. Islamic education curriculum development must consider values of Divine contained in the Qur’an and Sunnah besides that it should consider the development of human resources in order to have the ability to control and utilization and development in the field of science and technology. As well considering the technology available and can be used as a medium of learning.